The Grade 3 Provincial Achievement Tests: In Need of Revamping? - Roessingh, Hetty (Alberta Journal of Educational Research, 2012)
This article advances an argument for retaining but revamping the grade 3 Provincial Achievement Tests (PATs). Alberta’s demographic landscape is rapidly changing to include significant numbers of English language learners who are still in the early stages of developing English language proficiency at grade 3. Online tools are used to generate vocabulary profiles from exemplars of three standards of achievement: excellent, proficient and satisfactory. These are compared along various indices of vocabulary diversity. The findings provide striking evidence for rethinking the place of vocabulary in the overall assessment framework of the PATs, and in turn, for emphasizing the need for direct and explicit vocabulary instruction from the earliest of formal schooling experiences for immigrant children and the children of immigrants. Cet article avance un argument pour conserver, mais refaire, les examens provinciaux de la troisième année. Le paysage démographique de l’Alberta change rapidement en intégrant un nombre significatif d’apprenants de l’anglais qui en sont encore aux premières étapes de l’apprentissage de la langue anglaise en 3e année. Des outils enligne génèrent des profils lexicaux à partir d’exemples de trois niveaux de rendement; excellent, compétent et satisfaisant. Ceux-ci sont ensuite comparés en fonction de différents indices de diversité lexicale. Les résultats offrent des preuves convaincantes selon lesquelles il faudrait repenser la place du vocabulaire dans le cadre global d’évaluation des examens provinciaux. Ils soulignent le besoin pour un enseignement direct et explicit du vocabulaire dès le début de la scolarisation formelle des enfants immigrants et des enfants d’immigrants.